Peran Orang Tua dalam Pendidikan Seks pada Anak Usia 5-9 Tahun Di Nagari Tanjuang Bungo Kecamatan Suliki Kabupaten Lima Puluh Kota - Mega Ade Nugrahmi; Kartika Mariyona (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Sex education in early childhood aims for provide understanding to children regarding their reproductive organs, as well as matters concerning the differences between the two sexes and the introduction of dynamic body organs that the child can understand. Providing sex education is the obligation of parents for the future of their children to protect themselves from what has become the dignity of a child. Sex education is very useful because it considers the number of cases of sexual violence against children. This study aims to dig deeper into the role of parents in sex education for children in providing sexual education information according to the child's age group to reduce the high rate of sexual abuse to children. This research is qualitative, the participants are selected by purposive sampling technique. The research participants consisted of 4 people, namely Walinagari Tanjuang Bungo, Cadre, Parents and Children. The in-depth interview technique uses a recording device with a structured interview guide, as well as field notes. Data analysis used qualitative content analysis with collaizi approach. The role of parents in Nagari Tanjuang Bungo regarding sex education for children in introducing, expressing, sharing and guiding is still not perfect, because there are barrier factors, namely educational factors, economic and socio-cultural factors and family economic factors, which make parents busy with daily work activities. Days to provide for the family. As a result, parents forget about their role as parents in introducing sex education to children from an early age.